Explaining the model of comprehensive waste management in urban and rural areas and intermediate spaces (Case study: Khorasan Razavi province) - Shafaghi, Sirus (2021)
One of the main topics of sustainable development is environmental issues. Waste management is one of the most important environmental programs in the world. Today, statesmen have come to the conclusion that in order to achieve an ideal and sustainable society, it is necessary to pay attention to waste management. This study was conducted to identify the current status of waste management in Khorasan Razavi province and provide an optimal management model. This is a descriptive-analytical study. The sample population includes all cities and villages of Khorasan Razavi province. The sample size in cities with waste management organization was in full and in other cities and districts using random sampling method using Cochran's formula. The results were classified and analyzed using SPSS, Excel and GIS software. Data collection tools were library resources, field resources including interviews with experts, managers and professors of technology. Preparation and completion of questionnaires from urban and rural areas is the preparation of checklists and field visits. Based on the SWOT model strategy and internal and external environment analysis, the most important strength is the reduction of entrepreneurship in the implementation of waste management activities and the lack of a comprehensive plan for waste management is the most important weakness. In assessing the external environment, the existence of industries and markets for the consumption of recycled materials in the province and the region is the most important opportunity and the existence of economic crises in urban and rural communities and industrial areas in the region is the most important threat. The results of the study indicate the need to improve the framework and infrastructure of waste management in the province and the development of laws and detailed monitoring systems to implement the findings and scientific and practical experiences of other countries to achieve economic, social and environmental goals.